2022
DOI: 10.1101/2022.10.05.510928
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A novel antiviral formulation inhibits SARS-CoV-2 infection of human bronchial epithelium

Abstract: A novel proprietary formulation, ViruSAL, has previously been demonstrated to inhibit diverse enveloped viral infections in vitro and in vivo. We evaluated the ability of ViruSAL to inhibit SARS-CoV-2 infectivity, using physiologically relevant models of the human bronchial epithelium, to model early infection of the upper respiratory tract. ViruSAL potently inhibited SARS-CoV-2 infection of human bronchial epithelial cells cultured as an air-liquid interface (ALI) model, in a concentration- and time-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Commercial pan-species serology tests for SARS-CoV-2 are available and have been used in other studies of wildlife exposure to SARS-CoV-2 [31,33,34,68] . However, these kits are not validated for all species and we do not know what the cross-reactivity is with some of the more divergent coronaviruses detected recently in European wildlife [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Commercial pan-species serology tests for SARS-CoV-2 are available and have been used in other studies of wildlife exposure to SARS-CoV-2 [31,33,34,68] . However, these kits are not validated for all species and we do not know what the cross-reactivity is with some of the more divergent coronaviruses detected recently in European wildlife [42].…”
Section: Discussionmentioning
confidence: 99%
“…in Britain or mainland Europe [28][29][30] although other related coronaviruses have been detected in these species. Reports in European deer prior to 2022 all failed to detect any exposure [31][32][33], but 57 % of fallow deer in Dublin, Ireland, seroconverted in early 2022 [34] and sporadic seropositivity in fallow and red deer in Spain in 2021-22 has also been reported [35]. Wild animal surveillance studies in mainland Europe have indicated sporadic detection in wild mustelids, including by quantitative (q)PCR in wild American mink (N. vison), particularly near farmed mink outbreaks, and one otter (L. lutra) [36][37][38].…”
Section: Introductionmentioning
confidence: 99%